APPLICATION OF HYDROPHYILIC INTERACTIONS LIQUID CHROMATOGRAPHY FOR ORGANIC NITRATE ANALYSIS - A. S. Osipov; E. B. Nechaeva; L. A. Truhacheva (Разработка и регистрация лекарственных средств, 2019)
The possibility of the use of chromatographic columns with amino sorbents for the analysis of nitroglycerin and separation of isosorbide dinitrate and isomers of isosorbide mononitrate was investigated. As the mobile phase used a mixture of acetonitrile and water. Separation of analytes on amino columns in condition of the hydrophilic interaction liquid chromatography possible with acetonitrile content in the mobile phase, more 95%. Best separation isomers of isosorbide mononitrate on column Zorbax NH2, 150×4,6 mm was achieved with acetonitrile content in the mobile phase 99,8%. Separation of isosobide dinitrate and isosorbide mononitrates on columns with amino sorbents resulted in changing the sequence of elution of these compounds compared to reversed-phase chromatography.